Estudio comparativo de las especies: Dolichos lablad “abilla”, dolichos sp. “tada la vida” y passiflora edulis “maracuya” como mejora … - Yglesias Achjng, Nikol (2015)
Through this research work was able to determine which of the spec1es: "Abilla" (Do/ichos lablab), "Toda la Vida" (Do/ichos spp.), o "Maracuyá" (Passijlora edulis) contributes significantly to the improved landscape of the C. E. Maynas San Juan; for it the blocks design was realized completely at random by 03 treatments: TI: "Abilla" (Do/ichos lablab), T2: " Toda la Vida " (Do/ichos spp.), T3: "Maracuyá" (Passijlora edulis), being able to obtain 9 experimental units of 36 m2 (6x6) distributed in 03 blocks, with distancing from planting of 1 m between plants, with a total of 324 plants and the sampling unit of 16 plants per treatment, with a time of evaluation of 06 months between March and August, 2012. After evaluated and according to the obtained results it is determined that in regard to the vegetative development of the species "Abilla" Do/ichos lablab, " Toda la Vida " Do/ichos sp., and "Passion Fruit" Passijlora edulis, the kind that most contributes to improving landscape is the "Passion Fruit" Passijlora edulis, by presenting a higher production time (20 months), the higher plant height (324 cm.) larger sheets number (64 units), higher% of coveragelm2 (77 %), as well as biomass production. The "Maracuya" (Passijlora edulis) presents in three evaluated blocks maJor % Coverage with average value of 77 %1m2, followed by the "Abilla" (Do/ichos lablab) with 30 %1m2 and "the Toda la Vida Whole life" (Do/ichos sp.) with 45 %1m2. There is associativity between the height ofthe plant with the N° of sheets x plant in the case of the "Maracuya " (Passijlora edulis) that presents the greatest average height in the three blocks studied with a value of 324 cm., and 64 units, followed by the "Abilla" (Do/ichos lablab) with 303 cm., and 48 units and " Toda la Vida " (Do/ichos sp.) with 263 cm., and 42 units.